Síntese e caracterização de polímero de impressão iônica de acesso restrito para determinação on-line de cobre em leite - Naves, Daysla Fernanda Moreira (2022)
The determination of inorganic compounds in complex biological samples, such as milk, requires the use of techniques that are capable of presenting results with high sensitivity and selectivity. In this sense, the use of restricted access ion impression polymers (RAIIPs) for solid phase extraction (SPE) of metals, associated with flame atomic absorption spectrometry (FAAS) in a flow analysis system (FIA), is a good alternative to minimize interference effects, allow on-line separation and pre-concentration of samples, in addition to allowing the use of smaller amounts of sample volumes and reagents. Thus, this work aimed to carry out the synthesis and characterization of a Cu 2+ selective RAIIP to be used in an FIA-FAAS system for the online analysis of this ion in milk samples. RAIIP was synthesized by the bulk method, using Cu 2+ as template, 4-vinylpyridine as functional monomer, glycidyl methacrylate as hydrophilic co-monomer, ethylene glycol dimethacrylate as cross-linking agent, 4,4-azorbis (4-cyanovaleric acid) as radical initiator and acetonitrile as solvent. After the synthesis, the epoxide ring opening process was carried out to generate hydroxyl groups on the surface of the material, obtaining a RAIIP and later, the coating with bovine serum albumin was carried out, generating the RAIIP-BSA. The synthesized material was characterized by means of Fourier transform infrared spectroscopy and thermogravimetry to attest to the efficiency of synthesis and coating with BSA. After characterization, RAIIP-BSA was used in the on-line SPE of copper in copper samples. The main variables of extraction were optimized, with the best conditions being: sample pH: 7.0; sample volume: 20 mL, pre-concentration and elution flow rate: 5.5 mL.min -1 and eluent: HCl 1.0 mol.L -1 . The adsorption kinetics showed that the adsorption equilibrium is reached in 10 min and that the nonlinear model that best fit the experimental data was the pseudo-first order, being a physisorption process, that is, electrostatic attraction between Cu 2+ ions and RAIIP-BSA. The adsorption isotherm, in turn, was better adjusted to the Sips model, being a combination of the Langmuir and Freundlich isotherms. Through the selectivity tests, it was possible to conclude that the RAIIP-BSA shows improved selectivity to the ion of interest. The method was validated, showing good figures of merit, such as a linear range of 0.05 to 1.0 mg.L -1 , LoD and LoQ of 0.03 and 0.05 mg.L -1 , intra and inter- days ranging from 0.73 to 4.14% and 0.16 to 3.68%, respectively, and intra and inter-day accuracy ranging from 97.0 to 115.0% and 103.0 to 119% respectively. All milk samples analyzed were within the limits established by international and national legislation. Furthermore, the proposed method is capable of determining trace element concentrations with good accuracy and precision.